INDICES OF ENDOGENOUS INTOXICATION AT RABBITS WITH THE CHEMICAL BURN OF CORNEA AT THE BACKGROUND OF MERKAZOLIL-INDUCED HYPOTHYROIDISM - Савчук, З.Л. (World of Medicine and Biology, 2015)
To study the influence of experimental hypothyroidism on the state of endogenous intoxication at rats with the chemical burn of cornea markers of endogenous intoxication – molecules of average mass, erythrocyte and leukocyte indices of intoxication were determined. It was also investigated the activity of lysosomal proteases – cathepsin D and acid phosphatase. Hypothyroidism at rats was caused by the injection of merkazolil at a dose of 10 mg/kg for 60 days. Chemical burn of cornea was simulated by the application of filter paper saturated with 1 N NaOH for 30 seconds. Burning injury at rats at the background of hypothyroidism was accompanied by the suppression of the activity of lysosomal enzymes – cathepsin D and acid phosphatase in homogenate of cornea and more intense, as compared with euthyroid animals, markers of endogenous intoxication – molecules of average mass, erythrocyte and leukocyte indices of intoxication.
Keywords: chemical burns of the cornea; hypothyroidism; endogenous intoxication